2022
DOI: 10.1097/md.0000000000032155
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and clinical outcome of lateral wall fractures in proximal femoral fractures whose fracture line runs from femoral basal neck to subtrochanteric area

Abstract: Treatment methods for proximal femoral fractures, when the fractures run from the femoral basal neck to the subtrochanteric area, have not yet been fully reported. Thus, we aimed to clarify osteosynthesis methods based on the fracture frequency and clinical results. We classified the proximal femoral fractures using the Area classification method based on the location (area) of the fracture line. The proximal femur has 4 areas with 3 boundaries; the center of the femoral neck, the boundary between femoral neck… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In these cases, the preference is to use a cephalomedullary nail or P-FLCP 22 , 23 . If the lateral wall is already fractured pre-operatively (AO/OTA subtype-31A3), the general consensus from surgeons is to use an intramedullary nail 24 .…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, the preference is to use a cephalomedullary nail or P-FLCP 22 , 23 . If the lateral wall is already fractured pre-operatively (AO/OTA subtype-31A3), the general consensus from surgeons is to use an intramedullary nail 24 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recent studies have shown that posterolateral fracture lines of trochanteric femoral fractures cause posterolateral instability [11][12][13][14] . Kim et al and Suzuki et al reported that the presence of a posterolateral fracture increases the risk of postoperative fragment displacement, resulting in a higher rate of implant failure and/or nonunion 3,15 . However, the etiology of instability associated with a posterolateral fracture morphology remains unclear.…”
mentioning
confidence: 99%